Effect of depth of high-rate ponds on the assimilation of CO2 by microalgae cultivated in domestic sewage. Issue 20 (18th October 2018) - Couto, E. A.; Calijuri, M. L.; Assemany, P. P.; Souza, M. H. B.
ABSTRACT: This study evaluated the effect of high-rate ponds (HRPs) of different depths (20, 30 and 40 cm) on the carbon assimilation by microalgae cultivated in domestic sewage. The efficiency of the dissolution provided by the carbonation column and the carbon release to the atmosphere through the movement of the paddle wheels were also investigated. Dissolution efficiencies of 50%, 48% and 46% were obtained in the HRPs of 20, 30 and 40 cm depth, respectively. These differences can be attributed to the time necessary to recirculate the volume of each HRP in the carbonation column. The volumetric mass transfer coefficients regarding the release to the atmosphere were 0.0007, 0.0005 and 0.0004 min −1 for the 20, 30 and 40 cm HRPs, respectively. The carbon assimilation by the biomass was inversely proportional to depth, with values of 90%, 72% and 68% for the 20, 30 and 40 cm HRPs, respectively. Chlorophyll- a concentration was also higher in the 20 cm HRP. The radiation attenuation at the beginning of the operation was similar among the treatments, resulting in a greater fraction of the pond depth with available radiation in the 20 cm HRP.